Aristotle's Conception of the Artistic Unity of Homer's Epic and Rustaveli's "The Man in the Panther's Skin" - Zaza Khintibidze, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2026)
Research into the relationship of Aristotle's Poetics with the Man in the Panther's Skin (the MPS) of Rustaveli was commenced by Georgian philologists quite some time ago (see 1). The same may be said ni connection with the Iliad and the Odyssey (for details see 2). In recent times comparative-structural analysis of Rustaveli's poem and Homer's epic has also been carried out (see ;3 ;4 5). The purpose of the present paper is ot continue research in the above direction.